Peran Matematika dalam Kehidupan Sosial Masyarakat - Siregar, R.Maisaroh Rezyekiyah; Dewi, Izwita (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this study is to provide information about the role of mathematics in social society. The method of writing this article uses literature study by taking information sources from various data sources such as books, journals, and the internet. The author hopes that this article will add to the reader's insight about mathematics which has urgency with the development of social life, namely how mathematics is used to solve everyday human problems, and the relationship of mathematics to the progress of the times. In the economic development of society, mathematics provides such a large contribution, mathematics as a means of interacting socially. Both from buying and selling activities, banking, lending and borrowing, and other activities. Judging from the agricultural aspect, it turns out that farmers' activities are related to mathematics, namely measuring and calculating. From the aspect of education, mathematics has a consistent character in the system and adheres to principles. This means that there is no contradiction in mathematics in the system. Consistency is meant in terms of meaning and truth value. It is expected that students after studying mathematics can make students honest, consistent, and responsible characters.